2002
DOI: 10.1023/a:1024600905574
|View full text |Cite
|
Sign up to set email alerts
|

Serum uric acid and risk for development of hypertension and impaired fasting glucose or Type II diabetes in Japanese male office workers

Abstract: We examined the association of serum uric acid (SUA) with development of hypertension (blood pressure > or = 140/90 mmHg and/or medication for hypertension) and impaired fasting glucose (IFG) (a fasting plasma glucose level 6.1-6.9 mmol/l) or Type II (non-insulin-dependent) diabetes (a fasting plasma glucose level > or = 7.0 mmol/l and/or medication for diabetes) over a 6-year follow-up among 2310 Japanese male office workers aged 35-59 years who did not have hypertension, IFG, Type II diabetes, or past histor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
247
2
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 348 publications
(270 citation statements)
references
References 38 publications
16
247
2
5
Order By: Relevance
“…BP was found to increase across SUA tertiles in black women in South Africa, 33 and these investigators also showed an independent relation between SUA and vascular resistance in men. Our finding of an association between SUA and BP in young adults in Seychelles concurs with the findings in adults: a positive relationship between SUA levels and BP was found in most studies, 2,3,5,6 although not in all. 34,35 It is important that this association be corroborated in children and young adults because studies in older adults are prone to confounding by many factors such as treatment, co-morbidity, reverse causation and so on.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…BP was found to increase across SUA tertiles in black women in South Africa, 33 and these investigators also showed an independent relation between SUA and vascular resistance in men. Our finding of an association between SUA and BP in young adults in Seychelles concurs with the findings in adults: a positive relationship between SUA levels and BP was found in most studies, 2,3,5,6 although not in all. 34,35 It is important that this association be corroborated in children and young adults because studies in older adults are prone to confounding by many factors such as treatment, co-morbidity, reverse causation and so on.…”
Section: Discussionsupporting
confidence: 91%
“…[1][2][3][4][5][6] An independent SUA-BP association is further substantiated by the finding that BP was lowered upon treatment with allopurinol in a randomized controlled trial in adolescents. 24 Johnson et al 25 refer to two main mechanisms to Serum uric acid, blood pressure and adiposity T Lyngdoh et al account for a link between SUA and BP.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations